Uchwały problemowe organów stanowiących jednostek samorządu terytorialnego w sprawach etyki seksualnej - Maroń, Grzegorz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The paper deals with the legislative activity of local government bodies in relation to socalled „problem resolutions” The scope of the article covered over 50 resolutions on sexual ethics issues. Problem resolutions of municipal (county, regional) councils are sequentially discussed in the following sub-sections: gender ideology, public expression of the views of the LGBT movement, legalization of same-sex unions, pornography and prostitution. According to the author, the best form of control of the given resolutions is social control carried out by the residents of local communities within the framework of the electoral mechanism. Subjecting such resolutions to substantive review by the administrative courts would result in the judiciary’s entanglement in axiological, philosophical, historical and political disputes. Recognisable shortcomings in the functioning of the title institution should not obscure the importance of problem resolutions as a form of local government expression.
Problem resolutions of the governing bodies of local government on the question of sexual ethics
Keywords: problem resolution; local government; sexual ethics; gender; homosexualism; prostitution; pornography